Analysis of innovative and inquiry biology learning design in in-service teacher students - Fuad Jaya Miharja; Ahmad Fauzi; Lintang Zaine; Firly Diah Prabandari (University of Muhammadiyah Malang, 2024)
The implementation of the Kurikulum Merdeka strongly recommends a model based on inquiry or investigations carried out actively by students. This study was conducted to analyze the tendencies of permanent teacher students in developing inquiry-based learning and its correlation with students' critical thinking skills. This survey research uses students of the biology in-service teacher at the University of Muhammadiyah Malang as a sample. The variables measured in this research include the variety of methods used, the variety of ways of perceiving problems, student collaboration activities, and the learning instructional quality. Data collection uses survey instruments that have been validated and reliable. Instrument validation uses the product moment validity test, while the reliability test uses the Alpha-Cronbach’s formula. The data obtained were analyzed using the Spearman's Rho correlation formula. The research results showed that the methods most frequently applied were group discussions (90.08%), presentations (82.64%), and questions and answers (76.86%). The most common way of apperception is by asking about experiences (70.25%) and stimulating students to share experiences (33.38%). Furthermore, teachers also provide collaboration space in most learning activities amounting to 67.77%. However, most new students disseminated definitions of terms in the project (64.46%) rather than explaining how the project was carried out (52.89%). Furthermore, the student worksheets developed have dominant problem solving activities (84.30%), have relevance to the learning model (72.73%), and evaluation questions have led to HOTS optimization. The research results also show a strong positive correlation (ρ=0.431, p<0.001) which shows that the relevance of student worksheets is strongly related to student HOTS.